2020
DOI: 10.1039/d0sc01515f
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective B(3,4)–H arylation of o-carboranes by weak amide coordination at room temperature

Abstract: B–H: site-selective B(3,4)–H arylations were accomplished at room temperature by versatile palladium catalysis enabled by weakly coordinating amides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…According to the symmetry of the icosahedral carborane and the differences in electronegativity between carbon and boron elements, 10 B–H vertices can be divided into 4 regio groups for both o -carborane (B­(9,12), B­(8,10), B­(4,5,7,11), and B­(3,6)) and m -carborane (B­(9,10), B­(5,12), B­(4,6,8,11), and B­(2,3)) (Chart ). On consideration of the vertex charge of o -carborane (B­(9,12) > B­(8,10) > B­(4,5,7,11) > B­(3,6)), transition-metal complexes with different electronic natures were employed for catalytic site-selective cage B–H functionalization of o -carboranes: electron-rich transition-metal catalysts are used to activate electron-deficient cage B­(3,6)–H bonds; , electrophilic transition-metal catalysts are employed to activate electron-rich cage B­(8,9,10,12)–H bonds. , For the selective metalation of B­(4,5,7,11)–H bonds that lie between B­(3,6)–H and B­(8,9,10,12)–H vertices, a directing group is required to guide the electrophilic transition-metal catalysts. ,, On the other hand, such a charge distribution of carborane cages could promote the walking of the metal fragment on the cage from the viewpoint of intensely studied chain-walking and ring-walking processes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the symmetry of the icosahedral carborane and the differences in electronegativity between carbon and boron elements, 10 B–H vertices can be divided into 4 regio groups for both o -carborane (B­(9,12), B­(8,10), B­(4,5,7,11), and B­(3,6)) and m -carborane (B­(9,10), B­(5,12), B­(4,6,8,11), and B­(2,3)) (Chart ). On consideration of the vertex charge of o -carborane (B­(9,12) > B­(8,10) > B­(4,5,7,11) > B­(3,6)), transition-metal complexes with different electronic natures were employed for catalytic site-selective cage B–H functionalization of o -carboranes: electron-rich transition-metal catalysts are used to activate electron-deficient cage B­(3,6)–H bonds; , electrophilic transition-metal catalysts are employed to activate electron-rich cage B­(8,9,10,12)–H bonds. , For the selective metalation of B­(4,5,7,11)–H bonds that lie between B­(3,6)–H and B­(8,9,10,12)–H vertices, a directing group is required to guide the electrophilic transition-metal catalysts. ,, On the other hand, such a charge distribution of carborane cages could promote the walking of the metal fragment on the cage from the viewpoint of intensely studied chain-walking and ring-walking processes.…”
Section: Introductionmentioning
confidence: 99%
“…The organometallic B(3,6)ÀHa ctivation has been investigated by Hawthorne, [14] Herbhold, [15] Xie, [16] Jin [17] and our group. [18] In recent years, several B(3)ÀC coupling reactions withoutd irecting groups have been disclosed (Figure 1C,l eft), [19] whilethe limited substrate scope has impeded their further applications.S ince either B(3) or B(4) is adjacent to cage carbons and the carbon vertex itself can be easily decoratedc ompared with other boron vertices,X ie, [20] Duttwyler, [21] Ackermann [22] and Che [23] ando ur laboratory [24] installed DGs on cage carbon so that aseries BÀCcoupling products were generated. Among them, the carboxylic acid, imine, "transient" imine, bidentate amide DGs resulted in B(4)À or B(4,5)ÀCf ormation.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the other C cage should be blocked by alkyl or aryl to guarantee good yield and B(4) selectivity. [24b, 25] Ackerman reported the amide directedc onstruction of B(3)À or B(3,4)ÀAr, [22] while Che realized the syntheses of B (3,6)ÀCc oupling compounds by irremovable PAr 2 DG (Figure 1C,r ight). [23] In most cases, aryl bromide or aryl iodide works as the aryl source.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, employing a directing group into cage carbon or boron could facilitate the activation/functionalization of B­(4,5)–H bonds . However, the selective activation/functionalization of B­(3,6)–H bonds with electron-deficient characteristic is still an rarely explored subject …”
Section: Introductionmentioning
confidence: 99%